Saúde bucal em crianças com idade índice de cinco anos pertencentes a famílias em situação de pobreza beneficiadas pelo Programa Bolsa Família - Almeida, Ana Cecília Esmeraldo Barreira de (2014)
Dental caries is associated with many inequalities, which are social, geographic and the ones related to the access to health services. The aim of this study was to identify the epidemiology of caries in children of five years old of families who are benefited with the Bolsa Família Program and intervene through teaching self-care, aiming to prevent decay and treat it if necessary. This research has become the method that guided the development of diagnostics, identifying problems and seeking solutions. The study included 29 families with 32 children. Data collection was conducted through interviews; clinical examination of the children to observe the epidemiological profile of dental caries and treatment needs; demonstration of plaque to check IHOS; supervised tooth brushing and clinical treatment. These activities were accompanied by tactics of Health Education. Results show that the monthly household income is up to one minimum wage in 28 (97%) of the families studied. The education that prevails is incomplete elementary school to (15) of the mothers and 52% (13) 45% of the fathers. The mother is the person responsible for bringing the child to the health facility in 26 (90%) of the families and for teaching the 28 (88%) children about oral hygiene habits. Thus, one realizes the importance of the oral health team to devote time to the guidance and motivation of mothers and children in self-care. About the presence of dental caries, 12 children had decay, three had white spot caries and 17 had cavity decay. About those children, 11 (64.7%) had a mother who did not study or did not complete primary education. Related to the quality of oral hygiene of the 32 (100%) children studied, seven (21.9%) had satisfactory oral hygiene, 15 (46.9%) had regular oral hygiene and 10 (31.2%) children had poor or unsatisfactory oral hygiene. This interesting study was to increase access to oral health care and health education of the families who receive the Bolsa Família Program services.